Public Expenditure in Latin America : Trends and Key Policy Issues - Clements, Benedict; Faircloth, Christopher; Verhoeven, Marijn (Washington, D.C. : International Monetary Fund, 2007)
This paper examines trends in government spending in Latin America from the mid-1990s to 2006. It also examines key policy issues, including the cyclicality of spending, public investment, public employment, and social expenditures. It finds that primary expenditures have trended upward for the past ten years as a share of GDP, driven by increases in current spending, in particular for social expenditures. Fluctuations in real spending have continued to follow a procyclical pattern. The paper finds that there is substantial scope to improve the efficiency of public investment, public employment, and social spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet